PELATIHAN KOPERASI BAGI IBU-IBU PKK DALAM MENGGERAK UKM SEKTOR PARIWISATA DI PULAU NGENANG KOTA BATAM - Zahara Fatimah; Siska Maldin; Baktivillo Sianipar; Mohamad Nur Afriliandi Nasution (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
Servants do this because they know that this cooperative is very useful, so the community must take advantage of this cooperative where the benefits of communicating cooperatives to people or associations who still feel inadequate or need proper assistance that are not burdensome.This service is carried out by visiting the destination, which is a method of analysis and solving the problem by providing theoretical guidance, which this time took place on Ngenang Island, Batam in September 2022 and the participants were PKK women and Kopersi managementSince. Ngenang is an island whose village is in Nongsa sub-district, Batam City, Riau Archipelago, Indonesia. The area is 81.47 km², with a density of 18 people/km². There are 4 RTs and 1 RW with the smallest population in the city of Batam in 2022 of 1,473 people, snce 20 years ago, Ngenang Island has been touched by the government, especially the tourism service, but people's understanding is still too low. This cooperative on Ngenang Island has been formed since 2018 but has been neglected, on this island there is already a Joint Business Group (KUB) in the field of fishermen and Batik crafts.